Recreational off-highway vehicle crashes resulting in victims being treated at a regional trauma center: mechanisms and contributing factors - Charles A. Jennissen; Meaghan T. Reaney; Gerene M. Denning (BMC, 2020)
Abstract Background Recreational off-highway vehicles (ROVs) have become increasingly popular in recent years; however, crash epidemiology is not well described. ROVs travel at least 30 mph, and unlike all-terrain vehicles, have a rollover protective structure (ROPS) and seat belts or a harness system for occupants. This study's objective was to evaluate the demographics, mechanisms, injuries, and associated risk factors of ROV crashes. Methods A retrospective chart review was performed for patients of all ages with ROV-related injuries presenting to a Level 1 trauma center from 2004 to 2017. Cases were identified by ICD-9/10 codes and narrative searches. Person- and crash-related variables were examined in relation to injury outcomes including body area injured, injury severity score, and disposition (e.g. hospitalization, intensive care unit admission). Descriptive, bivariate (chi-square, Fishers exact test), and linear regression analyses were performed. Results Seventy-two patients with ROV-related injuries were identified. The number of injured patients increased over the study period (p < 0.01). Patients were 49% youth < 16 years old, 63% males, and 99% Caucasian. Half of the injured (51%) were passengers, with a higher proportion of youth being passengers (70%) as compared to adults (35%) (p < 0.01). Nearly one-third (30%) of crash victims < 16 years old were ROV drivers. Twenty-nine percent of all crashes occurred on roadways. Almost 40% of injured adults crashed at night, while all youth were injured during the day (p < 0.01). The primary crash mechanism was a rollover (67%). Only one patient was documented as being helmeted, and approximately one-fourth (24%) sustained head injuries and/or loss of consciousness. Other documented injuries included those to the face (20%), chest (22%), abdomen (11%), extremities (58%), and skin (51%). Over 90% of narratives were consistent with victims being unrestrained. Nearly three-fourths (74%) of victims were hospitalized and 26% required ICU care, one-half (53%) of these being children. Conclusions Although ROVs have ROPs, lack of helmet and safety belt use are reducing their benefit. Youth are a large proportion of those injured in ROV crashes, often while driving despite vehicle operation recommended only for those ≥16 years old. Increased public education is needed regarding proper safety measures while operating and riding ROVs.